LABOUR TURNOVER AND HUMAN RESOURCE DEVELOPMENT IN PRIVATE SECTOR BUSINESS: A COMPARATIVE STUDY OF JAPAN AND SRI LANKA - Godakandearachchi, C.C.S. (A thesis submitted for the Degree of Master of Arts, 2000)
This empirical study examines labour turnover and human resource development (HRD) in private sector companies in Sri Lanka in comparison with Japanese companies. Case study was based on 4 companies in financial sector, 2 from each country. In-depth interviews and structured questionnaires were administered to collect data from sample of executives. The qualitative and quantitative data were analyzed using contents analysis and grounded theory and %2 test, t test, etc. Labour turnover is higher at 5% significance level in Sri Lankan companies compared to that of Japanese companies. HRD systems of Sri Lankan companies have major differences where as Japanese companies' systems are similar. HRD systems and practices are changing in both the countries. The possibility of revamping the HRD systems of the private sector companies of Sri Lanka should be investigated in future studies. Further due consideration should be given to study the possibility of formation of a training institution of HR in national level. XI